1992
DOI: 10.1111/j.1524-4725.1992.tb02922.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Estrogens and Progesterone on the Venous System of the Lower Limbs in Women

Abstract: Treatments with estrogens and progestogens are suspected of causing vascular complications either directly or by metabolic consequences. Although many studies have demonstrated an increased incidence of arterial and deep venous thrombosis, since 1970 the dose of estrogens and progesterones have been lowered with a proportional lowering of side effects. After classification of estrogens and progestogens, we studied their peripheral vascular effects. In our study, we demonstrated that the effects of estroprogest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 14 publications
0
22
0
2
Order By: Relevance
“…As the venous wall is a key component of Virchow's triad required for the initiation of the thrombus ), more work is needed to understand how various estrogenic products affect both the endothelium and smooth muscle of veins to develop products with arterial protection but limited venous risks. Varicose veins represent a venous disorder that is associated with increases in circulating estrogen (Vin et al, 1992;Ciardullo et al, 2000). However, causality of this condition is complicated by various genetic components and physical factors such as obesity.…”
Section: Veinsmentioning
confidence: 99%
“…As the venous wall is a key component of Virchow's triad required for the initiation of the thrombus ), more work is needed to understand how various estrogenic products affect both the endothelium and smooth muscle of veins to develop products with arterial protection but limited venous risks. Varicose veins represent a venous disorder that is associated with increases in circulating estrogen (Vin et al, 1992;Ciardullo et al, 2000). However, causality of this condition is complicated by various genetic components and physical factors such as obesity.…”
Section: Veinsmentioning
confidence: 99%
“…The existence of positive family history and other factors such as orthostatism prolonged for Ͼ4 hours daily, 8 obesity, defined as a body mass index (BMI) Ͼ30 kg/m 2,6 ET, 14 and multiparity, 13 were considered as predisposing to CVD progression (Table I). We also documented preoperative ESU.…”
Section: Methodsmentioning
confidence: 99%
“…4 Several risk factors have been associated with the development of CVD, including older age, 5 female gender, 5,6 family history, 5,7 standing occupation, [8][9][10][11][12] obesity, 6,10-12 and multiparity. 7,10,12,13 However, other potential factors that may be involved in CVD progression have not been well studied, such as estrogen treatment (ET), 10,11,14 and warrant further investigation. On the other hand, although many studies have shown that elastic compression stockings are the keystone of CVD treatment in the context of symptom relief, 15 ulcer healing, 16 and antithrombotic prophylaxis, 17 limited evidence is present on supportive role of elastic stocking use (ESU) in the inhibition of CVD progression that is limited mainly to patients with post-thrombotic etiology.…”
mentioning
confidence: 98%
“…Hormonal changes that occur with aging and menopause appear to have a role, but the precise mechanisms remain ill-defined. [1][2][3] Since prior history or features of chronic venous disease (CVD) is usually absent, a venous cause is seldom investigated. Although other menopausal symptoms may be present, 1,4 the leg swelling is a dominant feature in many patients seeking specific treatment.…”
mentioning
confidence: 99%